Radio continuum emission in the northern Galactic plane: sources and spectral indices from the THOR survey - Wang, Yuan; Bihr, Simon; Beuther, Henrik; Klessen, Ralf S.; Linz, Hendrik; Glover, Simon; Bigiel, Frank (Astronomy and astrophysics, 2018)
Context: Radio continuum surveys of the Galactic plane can find and characterize H II regions, supernova remnants (SNRs), planetary nebulae (PNe), and extragalactic sources. A number of surveys at high angular resolution (≤25″) at different wavelengths exist to study the interstellar medium (ISM), but no comparable high-resolution and high-sensitivity survey exists at long radio wavelengths around 21 cm. Aims: Our goal is to investigate the 21 cm radio continuum emission in the northern Galactic plane at < 25″ resolution. Methods: We observed a large percentage of the Galactic plane in the first quadrant of the Milky Way (l = 14.0−67.4° and |b| ≤ 1.25°) with the Karl G. Jansky Very Large Array (VLA) in the C-configuration covering six continuum spectral windows (SPW). These data provide a detailed view on the compact as well as extended radio emission of our Galaxy and thousands of extragalactic background sources. Results: We used the BLOBCAT software and extracted 10 916 sources. After removing spurious source detections caused by the side lobes of the synthesized beam, we classified 10 387 sources as reliable detections. We smoothed the images to a common resolution of 25″ and extracted the peak flux density of each source in each SPW to determine the spectral indices α (assuming I(ν) ∝ να). By cross-matching with catalogs of HII regions, SNRs, PNe, and pulsars, we found radio counterparts for 840 HII regions, 52 SNRs, 164 PNe, and 38 pulsars. We found 79 continuum sources that are associated with X-ray sources. We identified 699 ultra-steep spectral sources (α < −1.3) that could be high-redshift galaxies. About 9000 of the sources we extracted are not classified specifically, but based on their spatial and spectral distribution, a large percentage of these are likely to be extragalactic background sources. More than 7750 sources do not have counterparts in the SIMBAD database and more than 3760 sources do not have counterparts in the NED database. Conclusions: Studying the long wavelengths centimeter continuum emission and the associated spectral indices allows us to characaterize a large percentage of Galactic and extragalactic radio sources in the area of the northern inner Milky Way. This database will be extremely useful for future studies of a diverse set of astrophysical objects.
Gesehen am 19.06.2019